Academic Entitlement in Physician Assistant Students. Issue 1 (March 2021) - Ellis, Jill; Bacon-Baguley, Theresa; Otieno, Sango
Abstract : Purpose: The purpose of this study was to identify the prevalence and characteristics of academic entitlement (AE) among physician assistant (PA) students in the United States. Methods: A cross-sectional survey design was used to assess AE using 2 previously validated AE surveys. Current PA students were recruited via email, and survey data were analyzed using descriptive statistics and cumulative logistic regression. Results: Overall, the 337 PA students who participated in the study reported low levels of AE. Students displayed the highest level of AE on statements related to the role of professors and the lowest level of entitlement on statements pertaining to student responsibility and grade entitlement. Students who struggled academically were more likely to report AE in relation to professors' roles. Older students were more likely to display AE related to provision of necessary resources by the university and less likely to display AE regarding the method of delivery for learning materials. Higher levels of grade-related AE were found in students in the didactic phase, female students, and students who did not identify as White. In addition, students who did not identify as White were more likely to display AE in relation to tests. Conclusions: Literature shows that AE has increased and is a major concern in higher education. Although the overall study results indicated relatively low AE, we found increased AE in certain student groups. Earlier identification of students at increased risk for AE would allow educators to intervene more effectively in a timely manner.